Pemberdayaan Ibu Rumah Tangga melalui Pembinaan Wirausaha Mandiri Pembuatan Sabun Milan dan Kerupuk Ampas Tahu - Sumiati Sumiati; Ratu Dea Mada (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2018)
One of activity occurred in Community Service Program of Unsera is workshop of entrepreneurship which involved the lectures as the supervisor. This workshop is done to established entrepreneurships among housewives in Sukamaju Village, Cikeusal District. We hope that the big numbers of housewives potency at this place can increase the salary for the household and support the needs of the household itself. This workshop produced soap called, Milan Soap and Tofu snacks with variant taste. This workshop also increase the economic level of the people in this place by producing soaps from house oil waste and tofu snacks from tofu waste and develop knowledge about entrepreneurships, accounting and marketing.